Increasing Students’ Motivation in Writing through Diving and Climbing Strategy - Minda, Sri (Association of Language Teachers in Southeast Asia (ALTSA), 2020)
This research aimed to find the effect of teaching strategy on the students’ motivation in writing and the students’ problems during the strategy implementation. Climbing and Diving was the strategy that was applied in this research. The design of the research is experimental. The first year students were taken as the population of the research. They are the Intensive language learning programme students in IAIN Padangsidimpuan. Questionnaire and interview were used to get the data. Likert scale was used in the questionnaire to score the students’ responses. From the calculation using t-test, the t value = 0.756 is the t table α = 0.05. It means that the students’ motivation in writing is significantly affected by Climbing and Diving strategy. During the implementation of the strategy, the students faced two dominant problems. They are time limitation and no specific pattern. The short time offered by this strategy does not give the students more chances to write and because of no pattern makes students lose control in writing.